Head positions are related to the performance quality of circles on pommel horse - Fujihara, T.; Gervais, P. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Enhancing the quality of circles is critical for pommel horse performance. Previous research as well as coaching literature emphasizes the importance of body alignment such as hip angle, but little attention has been attracted to head positions. Our purpose was to investigate the head-segment kinematics and its relation to other performance variables during circles on pommel horse. Through typical kinematic and correlational analysis of 18 participants, it was revealed that the skilled gymnasts moved their head significantly more backward in the rear support phase than the less skilled counterparts. The head positions in the rear support phase were correlated with the scores and also the performance variables such as body flexion angle, shoulder extension angle, and the horizontal diameter of shoulder trajectories.